The hidden heritage of Diaspora judaism: [essays on Jewish cultural identity in the Roman world] - Rutgers, Leonard Victor (Contributions to biblical exegesis and theology, 1998)
In recent scholarly debates concerning the history of the Jews in Roman times, the study of the Diaspora has begun to play an increasingly important part. New archaeological and inscriptional discoveries have provided scholars with much evidence to demonstrate that, in later Roman times, the majority of Jews lived outside the Land of Israel, in communities that could be found in virtually every corner of the Roman world. An investigation of how all these Jewish communities related to the Greco-Roman world surrounding them has become a central theme in the study of ancient Jewish history. In the present collection of essays, Dr. L.V. Rutgers, author of the award-winning The Jews in Late Ancient Rome (1995), investigates how Diaspora Jews defined their identity while interacting with temporary non-Jewish society. Bringing to bear on this issue archaeological, epigraphical, and historical evidence, the author investigates Jewish and non-Jewish evidence side-by-side in an attempt to shed new light on the question of how physical remains can help us to revise current perceptions of Jewish life in the Diaspora. In an introductory chapter Dr. Rutgers uses the evidence collected elsewhere in this book to argue that the Jews of antiquity must have had a very clearly defined sense of identity. Discussing some of the methodological problems that face scholars working in this particular field of study, Dr. Rutgers also questions the idea that variety is characteristic of Diaspora Judaism.